A carafe of red - Asher, Gerald (University of California Press, 2012)
Every wine has a story. In this collection of elegantly written essays from the past thirty years, updated with a new introduction and endnotes, renowned author Gerald Asher informs wine enthusiasts with insightful, engrossing accounts of wines from Europe and America that offer just as much for those who simply enjoy vivid evocations of people and places. Asher puts wine in its context by taking the reader on a series of discursive journeys that start with the carafe at his elbow. In his introduction, Asher says, "Wine ... draws on everything and leads everywhere." Whether the subject is a.